Solving Linear and Nonlinear Fractional Differential Equations Using Bees Algorithm - Aladool, Azzam S.Y.; Abed, Abdulrazzaq T. (Iraqi Journal of Science, 2023)
A numerical algorithm for solving linear and non-linear fractional differential equations is proposed based on the Bees algorithm and Chebyshev polynomials. The proposed algorithm was applied to a set of numerical examples. Faster results are obtained compared to the wavelet methods.